Formação de professores em Angola: o perfil do professor do ensino básico - Francisco Caloia Alfredo; Jussara Cristina Barboza Tortella (EccoS – Revista Científica)
The text is a result of the research, supported by Capes, about the learning evaluation to prepare teachers to the basic teaching in Angola, in the educative system reform of 2004 . Through a mixed approach, it analyzed documents, classroom obser - vations, interviews and questionnaires directed towards trainers and trainees. In this theoretical article, it is analyzed the context, the defining assumptions of the teachers training and the profiles of the trainer and trainee teachers, having as its basis official do - cuments used throughout the reform, articulated to the used referential. It is concluded that the teachers training is not far from the sociocultural context through which it ha - ppens. The educative praxis may reflect the education and the training that it proposes. Although the teachers training stresses technical aspects in its process, it does not go far from the political dimension and it is considered essential to understand and to valorize the multiple knowing, without forgetting to guarantee a high level training.